An evaluation of the Penutur Jati programme using Stufflebeam's cipp model through the perspective of the Malaysian English teachers / Aumi Rabihah Muslimin - Muslimin, Aumi Rabihah (2013)
The Penutur Jati programme is one of the initiatives under the MBMMBI policy. A report for the Penutur Jati programme under British Council, found that there are some differences around the way mentoring is understood, practiced and supported between the British Council in East Malaysia and other vendors (Brighton and SMR) in West Malaysia. With these differences the outcome may be different in one setting and another. Currently, little is known about the outcome of the Penutur Jati programme from the perspective of the Malaysian English teachers. The main purpose of the study is to evaluate the effectiveness of the Penutur Jati programme through the perspectives of mentors and the Malaysian English teachers involved in this programme using context, input, process and product components of the CIPP evaluation model developed by Stuflflebeam (1971). Interviews with the mentor and language officer was conducted and self reported teacher questionnaire were given to 46 teachers involved in the Penutur Jati programme from Jasin district to find out their perceptions on the programme. Documents were also examined in order to obtain detailed information about the Penutur Jati programme. While the data based on the questionnaire were analyzed through descriptive and inferential statistics, content analysis was carried out to analyze the qualitative data. Multivariate Analysis of Variances with Pillai’s Trace test was employed to investigate whether the significant differences among dependent variables across independent variables existed. The findings of the current study identified that there were some deficiencies in all the 4 stages of the evaluation process. Improvements were suggested in designing a pedagogical programme as in Penutur Jati Programme, administrator should consider teachers’ needs and involve all stakeholders in a sustainable planning of the programme and establishing robust mechanism for monitoring programme objectives.Mentor should also use appropriate training methods that will increase teachers’ capacity and confidence in teaching. Lastly in terms of training of the mentors, local customs and traditions and cultural belief should be included in their training so that they will understand local customs to avoid tension in relationship of mentor and the Malaysian English teachers.